Rechargeable lithium batteries : from fundamentals to applications - Franco, Alejandro A. (Cambridge, UK : Woodhead Publishing, 2015)
Rechargeable Lithium Batteries: From Fundamentals to Application provides an overview of rechargeable lithium batteries, from fundamental materials, though characterization and modeling, to applications. The market share of lithium ion batteries is fast increasing due to their high energy density and low maintenance requirements. Lithium air batteries have the potential for even higher energy densities, a requirement for the development of electric vehicles, and other types of rechargeable lithium battery are also in development. After an introductory chapter providing an overview of the main scientific and technological challenges posed by rechargeable Li batteries, Part One of this book reviews materials and characterization of rechargeable lithium batteries. Part Two covers performance and applications, discussing essential aspects such as battery management, battery safety and emerging rechargeable lithium battery technologies as well as medical and aerospace applications.
4.2.2.1. State of the art4.2.2.2. Alternative lithium salts; 4.2.3. Additives; 4.2.3.1. Alkyl phosphates; 4.2.3.2. Alkyl phosphonates; 4.2.3.3. Phosphazenes; 4.2.3.4. Hydrofluoroethers; 4.2.3.5. Fluorinated esters; 4.3. Ionic liquid electrolytes; 4.3.1. Ionic liquids; 4.3.2. IL-lithium salt electrolyte mixtures; 4.3.3. IL blends; 4.3.4. ILs as electrolyte additives; 4.4. Polymer electrolytes; 4.4.1. Introduction; 4.4.2. Gel polymer electrolytes; 4.4.2.1. Strong gel electrolytes; 4.4.2.2. Weak gel electrolytes; 4.4.3. Dry polymer electrolytes; 4.4.3.1. Modifications of the polymeric host
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed April 16, 2015).
Elsevier
Keywords: Lithium ion batteries; TECHNOLOGY & ENGINEERING / Mechanical; Lithium ion batteries; Electronic books; Electronic books